Paradigma Pengembangan Kurikulum Pendidikan Agama Islam di Sekolah (Analisis berbagai Kritik terhadap PAI) - Khuzaimah Khuzaimah (Institut Agama Islam Negeri Purwokerto, 2017)
The present Islamic Education have some weaknessess that there should be some ideas for innovation to foster its progress. In the early period, Islamic education was presented in mosques, but nowadays it has been developed into well-managed institution, i.e. school (madrasah). Beside madrasah, which is based on religion, Islamic education is also included to the curriculum of formal education, although the portion is not as much as in madrasah. Since Islamic education is still developing, there are many criticism addressed to Islamic education.